Analisis Faktor Fisik Dominan Teknik Standing Shot Atlet Bola Tangan Jawa Tengah - Jihan Fatahillah Annur; Rivan Saghita Pratama (Journal of Sport Coaching and Physical Education, 2024)
The Standing Shot Shooting Technique is a technique that is often used in handball games. In its use, Central Java male handball athletes often experience failure when performing the standing shot shooting technique. Based on this, there are problems in implementing the standing shot shooting technique, whether due to physical condition or other factors. This research aims to describe the dominant physical factors that determine the standing shot shooting technique. The population in this study were Central Java handball athletes, with sampling using total sampling, 50 Central Jawa male handball athletes were selected. The data collection method uses test and measurement techniques. The data analysis technique uses path analysis. The results of the research show that the dominant physical factor that determines the standing shot shooting technique is strength, with a T-value of 7.99; agility, with a T-value of 4.16; coordination, with a T-value of 5.35; and accuracy, with a T-value of 7.07. There are also variables that have a positive influence on the standing shot shooting technique, namely strength, power, flexibility, coordination, accuracy, and balance. Apart from that, the variables that have a negative influence are endurance, speed, agility, and reaction